Dilemma of interpreting the Tisza space in regional dimensions - Baranyi, Béla; Sinóros-Szabó, Botond (Acta Agraria Debreceniensis, 2013)
This study deals with the evaluation of an especially important area, since the Tisza river is the basis of the spatial organisation of the Great Plain, the main spatial structural axis of Eastern Hungary and also its ecologic corridor of continental significance. The Tisza is a river which connects five countries to each other and it has an enormous catchment area. Its longest section can be found in Hungary. Two million people live directly in the spatial environment of the river. The safety and favourable quality of life of these people have to be provided. This is a great challenge from the aspect of regional development, economic, technological improvement, the acceleration of innovation processes, as well as the establishment of natural and environmental harmony.